2012
DOI: 10.1016/j.seppur.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of solute–solute interactions in steroidal hormone removal by ultrafiltration membranes

Abstract: Micropollutant removal by membrane filtration is variable and can be influenced by the presence of organic matter. When considering removal mechanisms, many studies have focused on membrane adsorption and solute-foulant interactions; however, little is known regarding the influence of solute-solute interactions as these are typically difficult to quantify. In this study experimental organic matter-water partition coefficients (K OM ) were applied to quantify and elucidate the influence of solute-solute interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Specifically, a lower removal of sulfamethoxazole at peak loads in PAC/UF systems was achieved, presumably due to desorption processes from the membrane material. A review of such sorptive interactions for estrogen compounds on membrane surfaces has been published by Schäfer et al, (2011) as well as relevant findings related to impact of solute-solute interactions on UF filtration (Neale and Schäfer, 2012), Sheng et al, (2016) also reported interactions of CECs with an UF membrane and differences between removal by PAC applied alone and within an in-line PAC/UF hybrid process. However, the implications of the findings related to such interactions on PAC efficiency in the hybrid PAC/UF process and long-term performance remain unclear.…”
Section: Activated Carbon Applicationmentioning
confidence: 99%
“…Specifically, a lower removal of sulfamethoxazole at peak loads in PAC/UF systems was achieved, presumably due to desorption processes from the membrane material. A review of such sorptive interactions for estrogen compounds on membrane surfaces has been published by Schäfer et al, (2011) as well as relevant findings related to impact of solute-solute interactions on UF filtration (Neale and Schäfer, 2012), Sheng et al, (2016) also reported interactions of CECs with an UF membrane and differences between removal by PAC applied alone and within an in-line PAC/UF hybrid process. However, the implications of the findings related to such interactions on PAC efficiency in the hybrid PAC/UF process and long-term performance remain unclear.…”
Section: Activated Carbon Applicationmentioning
confidence: 99%
“…Jin et al (2007) also inferred that most of 54 the estrone-HA interactions took place on the membrane rather than in solution, explaining further 55 the poor removal estimation. Neale and Schäfer (2012) were able to quantify the contribution of 56 hormone-HA interactions on increased hormone removal by ultrafiltration (UF) in the presence of 57 HA by determining organic matter-water partition coefficients. Increasing HA concentration led to 58 more hormone partition onto HA and in turn to greater hormone removal by UF, demonstrating the 59 role of micropollutant-NOM interactions on micropollutant removal.…”
Section: Introduction 31mentioning
confidence: 99%
“…This drag force is the main driving force for adsorbed steroid hormone molecules to move along and exit the pores. The pure water permeability of VaCNT membranes (pore diameters of 1.7−3.3 nm) is reported and compared with commercial UF (pore diameters 1.6−5.4 nm, PL series, Millipore) 38 , 76 , 78 and NF membranes (NF270, Dupont, pore diameters 0.8 nm) 79 in Fig. 2A .…”
Section: Resultsmentioning
confidence: 99%